Development and transformation of collaborative networks in events. Issue 3 (3rd July 2017) - Ihm, Jennifer; Castillo, Elizabeth A.
ABSTRACT: This study examines the mechanisms by which and the reasons that leaders of non-profit organizations transform interorganizational collaborative networks through event attendance. Drawing from a two-wave survey, this study examines the interorganizational networks of 30 individuals who participated in both waves, along with the reported activities of 121 individuals who participated in the second wave of the survey. This mixed methods study found that events transformed participants' weak ties into strong ties and promoted development of collaborative networks. Further, the study found that participants' motivations for attending the event and following up with contacts afterward focused on sharing resources and deepening connections. Implications for understanding how events promote formation and transformation of collaborative networks are discussed.